Comparison of Effects of Local Anesthesia and Two-Point Acupressure on the Severity of Venipuncture Pain Among Hospitalized 6–12-Year-Old Children - Parisa Shahmohammadi Pour; Golnaz Foroogh Ameri; Majid Kazemi; Yones Jahani (Journal of Acupuncture & Meridian Studies, 2017)
The aim of the present study was to compare the effects of topical anesthesia and acupressure at the Yintang (Extra 1) and the Laogong (P-8) points on the severity of venipuncture pain among hospitalized 6–12-year-old children. A sample (n = 120) of 6–12-year-old hospitalized children was recruited from two teaching hospitals located in Rafsanjan, Iran. The children were allocated to the topical anesthesia, acupressure, and control groups. For children in the topical anesthesia and the acupressure groups, eutectic mixture of local anesthetic (EMLA) cream and two-point acupressure were used, respectively, prior to performing venipuncture, whereas children in the control group only received routine prevenipuncture care. The severity of venipuncture pain was evaluated 5 minutes after performing venipuncture by using the Face, Leg, Activity, Cry, and Consolability behavioral pain assessment scale. The findings revealed that pain severity in both experimental groups was significantly lower than that in the control group, whereas there was no significant difference between the experimental groups regarding pain severity. Although acupressure was as effective as topical anesthesia cream in alleviating children's venipuncture pain, nurses are recommending to use acupressure instead of pharmacological pain management agents because of its greater safety, cost-effectiveness, and applicability.